Application of Enzyme Preparation as a Coadjuvant in the Control of Foam Formation in the Bioethanol Industrial Fermentation Process - Buzo, Fernando Henrique [UNESP]; Cedeno, Fernando Roberto Paz [UNESP]; Brienzo, Michel [UNESP]; Masarin, Fernando [UNESP] (Springer Nature, 2024)
The industrial production of fuel ethanol is carried out by a fermentation process with yeast Saccharomyces cerevisiae commercial cell recycling resulting in excess foam formation. The present work aims to evaluate the performance of a commercial enzymatic preparation (FermaxTM) as a defoaming agent in industrial bioethanol process. The enzymatic preparation was applied concomitant with traditional chemicals. The application was carried out by pumping the enzymatic preparation into the fermentation tanks. Assay 1, in continuous mode in the treated yeast dilution tank, while assay 2, was conducted in batch mode, after sending the yeast to the fermentation tanks. The monitoring of the process was carried out by quantifying the indicators of a fermentation process. Assays 1 and 2 showed average reductions in the consumption of defoamer and dispersant of 26% and 37%, respectively. In the assay 1, the strategy of reducing the mix of ethanol production was adopted, resulting in reductions in wort flow, ethanol production, and rate of occupation of tanks. Assay 1 resulted in similar values to the traditional process without the addition of enzyme. However, in assay 2, the strategy to reduce the ethanol production mix was not adopted. In this condition, there were no significant differences in the indicators of the fermentation process between the control and enzyme periods. Assay 1 presented a net cost reduction of 15%, while assay 2 presented a net cost increase of 9%, with resources for the acquisition of chemical inputs, which totaled savings of R$ 0.40 in assay 1 and a loss of R$ 0.18 in assay 2 per cubic meter of ethanol. The decrease in the ethanol production mix was the most appropriate moment for the application of the enzyme preparation.
Keywords: Defoamer; Dispersant; Excess foam formation; FermaxTM; Industrial bioethanol process